HUKUM POLIGAMI DALAM PERSPEKTIF ULAMA FIQH - Aris Baidhowi (MUWAZAH : jurnal kajian gender, 2012)
The fiqh ulama agree that the legal permissibility of polygamy in marriage is based on the word of Allah SWT, Surah of al-Nisa 'verse 3, which confirms that the polygamist husband conditions shall be fair to his wives. They recognize the value of justice in polygamy is something that is impossible to be realized. Therefore, the illat of legal permissibility of polygamy in Islam marriage is: that it shall not be encouraged by the motivation of biological sex and pleasure, but only by social and human motivation, since the interpretation of "able to do justice" as a basic requirement of polygamy allowance is very difficult. The permissibility of polygamy is not a recommendation; but it is a solution given in special conditions to them (husbands) who desperately need and meet certain requirements.